Transmission of CRC Bits with Rotated Polar Coded Signals - Chen, Haowei; Yao, Xinyuanmeng; Wei, Baodian; Ma, Xiao (2022 IEEE/CIC International Conference on Communications in China (ICCC), 2022)
In this paper, we propose a transmission scheme of cyclic redundancy check (eRe) bits with rotated polar coded signals and present the corresponding list decoding algorithm. An information bit sequence is encoded by a CRC encoder, resulting in CRC bits. The CRC bits are divided into two parts. One is transmitted by a rotated constellation scheme and the other with the information bit sequence is encoded by a polar encoder. We present a list decoding algorithm to detect the part of the CRC bits transmitted by the rotated constellation scheme. To reduce the decoding complexity, an early termination scheme is proposed. Simulation results show that the polar codes with 5G standard sequence using the proposed transmission scheme can obtain a performance gain of 0.75 dB compared with the conventional CRC-polar coded modulation.